TIPOGRAFI INKLUSIF SEBAGAI STRATEGI AKSESIBILITAS VISUAL DALAM KOMUNIKASI DIGITAL: STUDI KASUS TYPEFACE INCLUSIVE SANS: Inclusive Typography as a Visual Accessibility Strategy in Digital Communication: A Case Study of the Inclusive Sans Typeface - Muhammad Peby Mardiansyah; Ganis Resmisari (Universitas Trisakti, 2026)
Inclusive Typography as a Visual Accessibility Strategy in Digital Communication: A Case Study of the Inclusive Sans Typeface. Visual accessibility has emerged as a crucial issue in digital communication, especially with the increasing dependence of society on screen media. However, digital typography design practices still tend to prioritize visual standards for users with normal vision, thereby potentially creating barriers for individuals with visual impairments or different ways of processing information. Inclusive typography has emerged as a design approach that places accessibility as a key principle in the formation of letter structures. This study aims to analyze how the principles of inclusive typography can be realized visually in the Inclusive Sans typeface, as well as its role as an approach to visual accessibility in the context of digital communication. Using a qualitative-descriptive method through case studies, this research involves visual typography analysis and targeted literature studies. The analysis focuses on visual elements that theoretically affect readability and legibility, including their relationship with inclusive design principles and accessibility guidelines. The findings reveal that Inclusive Sans indicates the application of inclusive typography through clear character differentiation, consistent letter structure, open counters, and proportions and spacing oriented towards legibility in a digital environment. These findings reinforce that typography can serve as a visual communication strategy that has the potential to support accessibility, while also broadening the understanding of typography's role as a visual system with social and cognitive impacts in digital communication design.